Blended Synchronous and Asynchronous Learning: Its Effectiveness for Teaching Grammar - Mukminatus Zuhriyah; Elisa Nurul Laili (English Department FBS UNP, 2022)
The online EFL teaching and learning in this COVID-19 pandemic era has been conducted synchronously and asynchronously. However, the implementation of blended synchronous and asynchronous learning in the online grammar class was still scarce. Therefore, this study was conducted with the purpose of knowing whether or not the use of blended synchronous and asynchronous learning was effective for teaching grammar. This study was a pre-experimental research using one-group pretest-posttest design. The population of this study was the students of the second semester in the English department of a private university located in East Java. Because there was only one class in this second semester so that the sample was the same as this population. There were fifteen students in this sample. In collecting the data, the researchers used the pretest and posttest of grammar. After the data of pretest and posttest were in the normal distribution, the testing of hyphothesis using t-test especially paired samples test was conducted. The result of this t-test showed that the Sig. (2-tailed) 0.000 was lower than 0.05. It revealed that the difference of the mean scores of pretest and posttest was significant. Thus, the use of blended synchronous and asynchronous learning was effective for teaching grammar.